Late Jurassic Elasmobranch and Actynopterigian fishes from Portugal and Spain. - Kriwet, J. (Cuadernos de Geología Ibérica, 1998)
The present paper gives a survey of Late Jurassic fishes from Portugal and Spain. For the first time 4w complete ichthyofauna of the Guimarota coal mine in central Portugal is presented. Ihe material consists of isolated teeth, placoid scales, fin and head-spines of elasmobranchs (Asteracanthus, Hybodus, Polvacrodus, Scyliorbinidae, Rajiformes) and isolated teeth, jaw elements, cranial and postcranial material of actinopterygians (Semionotiformes, Pycnodontiformes, Macrosemiiformes, Ionoscopidae, Amiiformes, Pachycormiformes, Actionpterygii ¡ndet.). The material is dated as early Kimmeridgian. New material from the marine Late Jurassic (Oxfordian to Tithonian) of the central Ibcrian Chain is briefly described. It consists of isolated teeth and scales. Neoselachians (Nótidanoides, Squalogaleus, Squatina, 7Heterodontus, Orectolobiformes, Scyliorhinidae, Rajiformes) and actinopterygians (Ionoscopidae. Caturidae, Aspidorhynchiformes) are reported for (he first time in the Late Jurassic of (he central pan of the Iberian Basin.